Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41467-020-17098-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into chromatin targeting by leukemic NUP98-PHF23 fusion

Abstract: Chromosomal NUP98-PHF23 translocation is associated with an aggressive form of acute myeloid leukemia (AML) and poor survival rate. Here, we report the molecular mechanisms by which NUP98-PHF23 recognizes the histone mark H3K4me3 and is inhibited by small molecule compounds, including disulfiram that directly targets the PHD finger of PHF23 (PHF23PHD). Our data support a critical role for the PHD fingers of NUP98-PHF23, and related NUP98-KDM5A and NUP98-BPTF fusions in driving leukemogenesis, and demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Notably, our results revealed a significant coexistence of the three factors at gene promoters ( Fig. 4 A and B ), which is in good agreement with previous reports that the C-terminal PHD finger domain of Kdm5b directly binds H3K4me3 ( 21 , 22 ) and that Kdm5b binding sites overlap H3K4me3 in different cell models ( 23 , 24 ); also, chimeric NUP98 fusion oncoproteins (NUP98-NSD1 or NUP98-PHD) were found targeted to promoters for oncogene activation ( 7 , 25 27 ). Integrated analyses of our ChIP-seq and RNA-seq datasets in NUP98-NSD1 + AML cells further defined genes that are cotargeted by both Kdm5b and NUP98-NSD1 and also transcriptionally repressed by Kdm5b ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Notably, our results revealed a significant coexistence of the three factors at gene promoters ( Fig. 4 A and B ), which is in good agreement with previous reports that the C-terminal PHD finger domain of Kdm5b directly binds H3K4me3 ( 21 , 22 ) and that Kdm5b binding sites overlap H3K4me3 in different cell models ( 23 , 24 ); also, chimeric NUP98 fusion oncoproteins (NUP98-NSD1 or NUP98-PHD) were found targeted to promoters for oncogene activation ( 7 , 25 27 ). Integrated analyses of our ChIP-seq and RNA-seq datasets in NUP98-NSD1 + AML cells further defined genes that are cotargeted by both Kdm5b and NUP98-NSD1 and also transcriptionally repressed by Kdm5b ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with these chromatin rearrangements, a chromosome conformation analysis using Hi-C revealed that NHA9 induced the organization of an aberrant 3D chromatin structure during cellular transformation that was enriched in proto-oncogenes [ 56 ]. Our data further strengthened the notion that N98 fusion proteins and N98 bind to H3K4me3 residues, likely due to the interaction with MLL [ 41 , 42 , 43 , 44 , 61 , 66 ].…”
Section: Discussionsupporting
confidence: 83%
“…Given the architectural effects of NHA9 on nuclear organization, we next asked whether these changes provoked by NHA9 translate into changes in chromatin structure, as not only are LAP2α and LA/C known to be involved in the regulation of chromatin [ 37 , 38 , 39 ], but also RB itself has important chromatin regulatory functions [ 37 , 38 , 54 ]. As a read-out for the analysis of chromatin structure, we decided to analyze the pattern of some histone modifications, known to be correlated to N98, NHA9, RB, and/or LAP2α, i.e., trimethylation of histone H3K4, H3K27, as well as H3K9 [ 4 , 12 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. To explore the impact of NHA9 expression on histone methylation in an RB-dependent manner, we transiently expressed GFP-NHA9 in HCT-116 cells and proceeded with immunofluorescence analysis of H3K27me3 and H3K4me3 deposition under these conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…were through association with H3K4me2/3 marks (Zhang et al, 2020). Thus, the chromatin reader type NUP98 fusions confer a targeting ability to the chromatin of the HOX-A loci by interacting with specific chromatin modifications and/or chromatin binding proteins.…”
Section: Discussionmentioning
confidence: 99%